2019
DOI: 10.1016/j.lwt.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Bee bread as a functional product: Chemical composition and bioactive properties

Abstract: Bee bread is a mixture of pollen pellets, honey and lactic acid bacteria, and the basis of food in the hive. In the present study, a Moroccan bee bread has been analyzed concerning the palynological analysis, nutritional value and chemical composition (free sugars, organic acids, mineral composition, fatty acid, tocopherols and polyphenols); in vitro antioxidant activity and antimicrobial activity screened against pathogenic bacteria and fungi were also evaluated. The studied bee bread was a good source of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
145
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(169 citation statements)
references
References 32 publications
(41 reference statements)
18
145
4
2
Order By: Relevance
“…The fat content and ash content were found in a lower concentration than carbohydrates and proteins. The bee bread energy (412.07 Kcal/100 g) is higher than the value reported by Bakour et al [ 8 ] in Moroccan bee bread. The fat content of bee bread reported in the literature ranged differently, as follows: 1.90% in Moroccan bee bread [ 8 ], 5.93% to 11.55% in clover, cotton, chestnut, citrus, and sunflower bee bread from Turkey [ 17 ], and 4.51% to 4.92% in Colombian bee bread [ 7 ].…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…The fat content and ash content were found in a lower concentration than carbohydrates and proteins. The bee bread energy (412.07 Kcal/100 g) is higher than the value reported by Bakour et al [ 8 ] in Moroccan bee bread. The fat content of bee bread reported in the literature ranged differently, as follows: 1.90% in Moroccan bee bread [ 8 ], 5.93% to 11.55% in clover, cotton, chestnut, citrus, and sunflower bee bread from Turkey [ 17 ], and 4.51% to 4.92% in Colombian bee bread [ 7 ].…”
Section: Resultscontrasting
confidence: 67%
“…Bee bread is the main food for the beehive, and particularly for larvae and young worker bees that produce royal jelly [ 3 ]. It can be considered an important source of nutrients and bioactive compounds such as proteins, vitamins (C, B, K, P and E), and polyphenols (flavonoids, phenolic acids) which are influenced by the source of pollen and different factors that influence the growth of the pollen plant (geographic origin, soil, climate) [ 6 , 7 , 8 ]. The studies carried out on volatile profile components showed a high concentration of unsaturated aliphatic acids, amino acids, terpene and terpene derivates, carbohydrates (e.g., glucose, fructose), and nitriles [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Belina-Aldemita et al [4] also found high amount of potassium and sodium in pot pollen of T. biroi in Philippines. is result is also in agreement with those of Bakour et al [21] as potassium was the main mineral in Moroccan bee bread with the value of 338 mg/ 100 g, followed by phosphorus (251 mg/100 g).…”
Section: Samplingsupporting
confidence: 93%
“…e energy values of H. itama bee bread obtained were between 367.33 and 371.00 kcal/100 g. ese values were higher compared to those of bee bread samples of M. seminigra (350.57 kcal/100 g) and M. interrupta (331.33 kcal/ 100 g) from Brazil [35] and T. biroi (216 to 266 kcal/100 g) from Philippines [4] but lower than those of bee bread from Morocco (396.2 kcal/100 g) [21].…”
Section: Physicochemical Analysismentioning
confidence: 73%
See 1 more Smart Citation